Impact of the COVID-19 pandemic on school-based agricultural education (SBAE) teachers’ job satisfaction and work-life balance - Hoelting, Kelly R. (Kansas State University, 2022)
The COVID-19 pandemic created the largest disruption of education systems in human history, affecting nearly 1.6 billion learners in more than 200 countries (Pokhrel & Chhetri, 2021). By the end of March 2020, more than 124,000 U.S. public and private school buildinsg experienced closure affecting 55.1 million U.S. children and over 80 percent of the world’s student population (Sahu, 2020; Van Lancker & Parolin, 2020). The new standard operating procedures disrupted traditional education practices and presented another set of challenges for educators (Pokhrel, & Chhetri, 2021). Within a short span of the COVID-19 pandemic, many researchers have shared their works on teaching and learning in different ways, but as we have reopened and began easing restrictions, there is little research on how the pandemic affected school-based agricultural education (SBAE) teachers and programs. This study provided a point-in time for the lasting impact of this historical event on SBAE teachers in National Association of Agricultural Educators (NAAE) Region II. The purpose of the study was to investigate how the COVID-19 pandemic impacted the overall job satisfaction and the overall work-life balance of School-Based Agricultural Education (SBAE) teachers. The study also examined limitations, challenges, and additional life roles teachers faced during the pandemic and the impact on their stress level and plans to return to the agricultural education classroom. The role conflict theory (Greenhaus & Beutell, 1985) and the conservation of resources theory (Grandey & Cropanzano, 1999) were used as the theoretical framework for the study. The results of the study indicate SBAE teachers have a lower overall job satisfaction and lower overall work-life balance while teaching during the COVID-19 pandemic. SBAE teachers reported an increase in stress levels during the pandemic, which may contribute to a lower job satisfaction and retention rate of agricultural education teachers. SBAE teachers were able to give descriptive data throughout the study of how they were impacted, why they have chosen to stay in the agricultural education classroom and the changes made in their SBAE programs due to the COVID-19 pandemic. These responses help to give an insight into how we can provide support for our agricultural education teachers and understand the challenges they may face in the future. Recommendations from this study should be used in the creation of professional development programs to prepare SBAE teachers for educational disruptions while maintaining a high satisfaction rate with their job.
Keywords: COVID-19; Agricultural education; Pandemic; SBAE; Agriculture